Defining Biochemical Cure After Low Dose Rate Prostate Brachytherapy: External Validation of 4-year Prostate-specific Antigen Nadir as a Predictor of 10- and 15-year Disease-free Survival. Issue 1 (January 2022) - Noble, D.J.; Doyle, E.; Tramonti, G.; Law, A.B.; Sundaramurthy, A.; Brush, J.P.; Keanie, J.; Wood, C.; Drewell, P.; Keough, W.; McLaren, D.B.
Abstract: Aims: To externally validate a proposed biochemical definition of cure following low dose rate (LDR) brachytherapy for prostate cancer – 4-year post-implant prostate-specific antigen (PSA) ≤0.2 ng/ml – in a UK population, and report the long-term (10- and 15-year) outcomes for patients stratified by National Comprehensive Cancer Network (NCCN) risk groups, through analysis of a large, prospectively collected, single-centre database. Materials and methods: All patients treated with LDR brachytherapy for prostate cancer at a single UK centre between 2001 and November 2020 ( n = 1142) were eligible; 632 patients met the inclusion criteria for the analysis. The primary end point was disease-free survival (DFS), defined as freedom from clinical, radiological or PSA progression requiring androgen deprivation therapy. Four-year PSA was categorised as ≤0.2, >0.2 to ≤0.5, >0.5 to ≤1.0 and >1.0 ng/ml. Kaplan–Meier analysis to 15 years was undertaken for each group, and sensitivity and specificity of 4-year PSA as a surrogate for long-term cure were calculated. Kaplan–Meier analysis to 15 years was repeated, stratifying patients by NCCN risk groups. Results: The median cohort age was 63 years; the median follow-up was 9.1 years (range 3.5–18.7). In total, 248 patients were available for analysis at year 10, 46 at year 15. Sixty-four patients (10.1%) relapsed during the study period. The 10-year DFS for 4-year PSA categories ≤0.2, >0.2 to ≤0.5, >0.5 to ≤1.0 and >1.0 ng/ml (95% confidence intervals) were 97.5% (95.4–99.6), 89.0% (82.4–96.1), 81.5% (70.5–94.2) and 41.8% (29.7–58.9), respectively. The 10-year DFS results for NCCN low, favourable-intermediate and unfavourable-intermediate risk disease were 93.1% (89.6–96.7), 92.1% (87.6–96.9) and 75.9% (67.8–84.9), respectively. Conclusions: Patients with 4-year PSA ≤0.2 ng/ml may be considered cured, and could be discharged to general practitioner follow-up. LDR brachytherapy is an excellent treatment option for patients with low and favourable-intermediate risk prostate cancer, but those with unfavourable-intermediate risk disease should be considered for treatment intensification strategies. Highlights: 15-year follow-up data following LDR brachytherapy for prostate cancer 97.5% of patients with 4-year PSA ≤ 0.2 ng/ml disease free 10 years post-implant 4-year PSA ≤ 0.2 ng/ml equates to cure for these patients; safe to discharge to GP 10-year DFS > 90% for patients with low and favourable-intermediate risk prostate cancer 75.9% 10-year DFS for unfavourable-intermediate risk